Implementation of the Religious Moderation Program to Realizing the Project Student Profile Pancasila and Rahmatan Lil Alamin (P5 and PPRA) in Madrasah - Hamam Burhanuddin; M. Imron (Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2023)
This research will focus on Strengthening the principles of religious moderation in the Islamic education, multicultural values in education and strategies for developing religious moderation to realizing P5 PPRA. The method a qualitative descriptive approach, collecting data with observation, interviews and documentation, the validity of data credibility, transferability, dependability, and certainty. Result The internalization of religious moderation values in realizing the Project to Strengthen the Pancasila Student Profile (P5) and the Rahmatan lil’alamin Student Profile (PPRA) at carried out through co-curricular activities, integration into learning activities, and extracurricular activities focused on three values: nationalism, diversity, and tolerance through transformation, trans internalization, and the transaction of values, The values of religious moderation instilled in students are the values of Tasamuh (tolerance) and ”˜Adalah (justice), which are principles taught to the students.